2004
DOI: 10.5194/angeo-22-747-2004
|View full text |Cite
|
Sign up to set email alerts
|

Location accuracy of long distance VLF lightning locationnetwork

Abstract: Abstract. An experimental VLF WorldWide Lightning Location (WWLL) network is being developed to provide realtime locations of cloud to ground lightning discharges occurring throughout the globe. This network has expanded from a limited number of stations in the Western Pacific to its current state of 11 stations, in most longitude sectors, with additional stations planned in the near future. As part of the initial testing phase of the WWLL the network has operated in a simple mode, sending the station trigger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(86 citation statements)
references
References 26 publications
3
83
0
Order By: Relevance
“…the Australian Kattron data of Rodger et al (2004Rodger et al ( , 2005 had 1 ms timing at best), while the WWLLN data has 1 µs resolution which is sufficient to meet its DE needs. In order to make comparisons between the location estimates for CG lightning discharges by the NZLDN and WWLLN network data, WWLLN events were selected which occurred within ±0.5 ms of a lightning event detected by NZLDN inside the selected region.…”
Section: Nzldn Lightning Location Datamentioning
confidence: 99%
See 1 more Smart Citation
“…the Australian Kattron data of Rodger et al (2004Rodger et al ( , 2005 had 1 ms timing at best), while the WWLLN data has 1 µs resolution which is sufficient to meet its DE needs. In order to make comparisons between the location estimates for CG lightning discharges by the NZLDN and WWLLN network data, WWLLN events were selected which occurred within ±0.5 ms of a lightning event detected by NZLDN inside the selected region.…”
Section: Nzldn Lightning Location Datamentioning
confidence: 99%
“…The location accuracy and regional detection efficiency of the WWLLN network has been examined by contrasting its observations with those from MF/HF lightning detection networks in Australia, Brazil, and America (e.g., Lay et al, 2004;Rodger et al, 2004Rodger et al, , 2005Jacobson et al, 2006). These studies indicated that WWLLN does indeed detect strong lightning discharges in various parts of the Earth, and produced estimates for the global location accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…We used data from the World Wide Lightning Location Network (WWLLN) to locate lightning flashes during the time of most intense convection. WWLLN has a detection efficiency of approximately 20 % in our study region (Rodger et al, 2009) and a location accuracy of 5-10 km (Rodger et al, 2004). Despite this limited detection, previous studies have successfully used the data to locate deep convection (e.g., Abarca et al, 2010).…”
Section: Mesoscale Featuresmentioning
confidence: 99%
“…The dispersed waveform (the so-called "sferic") of the lightning impulse is processed at each receiving site and the location of the lightning is determined based on the time of group arrival of the VLF waves, detected at more than five stations (Dowden et al 2002). The WWLLN algorithm can detect lightning with a 5-km spatial accuracy and 15-µs temporal accuracy, and its detection efficiency is 11% for all strokes and > 30% for more powerful strokes (Rodger et al 2004;Abarca et al 2010). …”
Section: Datamentioning
confidence: 99%
“…Because detection efficiency is higher for stronger strokes (Rodger et al 2004;Abarca et al 2010) and because the minimum detectable stroke energy of each lightning stroke depends on the minimum observable energy of each WWLLN station (Hutchins et al 2012b), the reliability of data for weak stroke energy is considered insufficient. Therefore, we focus on lightning with strong stroke energy.…”
Section: Seasonal Variation Of Lightningmentioning
confidence: 99%